Bahasa Indonesia Roadside Sweeper Pada Tepi Jalan Raya Menggunakan Motor Listrik DC - Rachmad Ikhsan; Zoel Fachri; Teuku Syukri (J-Innovation, 2023)
Roadside sweeper is a tool that can sweep garbage in the form of leaves or small tree branches on the roadside. Roadside sweeper designed to use a DC electric motor as the driving force. This roadside sweeper also uses an emergency button for emergencies such as garbage getting stuck in a shelter which causes the driving motor to stop and stall. After testing the sweeper components and sweeper motor on the frame, it is known that the sweeper components and sweeper motor can function optimally, at a voltage of 12 Volts. From the test results it was also found that with a battery power of 3.5 Ah the Roadside Sweeper tool can work for 126 minutes and can run properly. This Roadside Sweeper tool can be concluded that to clean the roadside with optimal cleanliness, this tool must do 2 times of rotation to get satisfactory results.